Linguistic Markers of the Emotion Elaboration Surrounding the Confinement Period in the Italian Epicenter of COVID-19 Outbreak - Negri, Attà; Andreoli, Giovanbattista; Barazzetti, Arianna; Zamin, Claudia; Christian, Christopher (Frontiers in Psychology, 2020)
The expressive writing method has rarely been proposed in contexts of large-scale upheavals that affect large populations. In this study this method was applied as an intervention and investigation tool during the confinement period in Lombardy region, the Italian Epicenter of COVID-19 outbreak. Sixty-four participants took part in an online expressive writing project, and a total of 167 writings were collected together with some self-report evaluations on emotions and physical sensations. A linguistic analysis through two different sets of computerized linguistic measures was conducted on the writings collected in order to study the linguistic markers of emotion regulation and elaboration. Results indicated that online expressive writing has helped respondents to get more in touch with the intense emotions experimented following the upheavals they witnessed. Writing even only once or twice helped, in particular respondents who had at least one COVID-19 patient among close friends or relatives. Their writings showed an intense emotional involvement together with the ability to reflect and reorganize the personal meaning of the events and emotions experienced. This study shows that expressive writing can be used in the context of a psychological emergency, both as a powerful instrument to investigate and detect the complex psychodynamic processes underpinning the distress, and as a useful intervention to reduce the negative impact of traumatic events.